Mugabest Implementasi Pendekatan Whole Language dalam Meningkatkan Kemampuan Bercerita Siswa Melalui Media Gambar Ebook di Kelas V SD (International Forum of Researchers and Lecturers, 2025)
This study aims to improve elementary school students' storytelling skills through the application of the Whole Language approach combined with ebook-based image media. The Whole Language approach was chosen because it emphasizes the integration of natural language skills in meaningful contexts, while the ebook-based image media was used to provide engaging visual stimuli, facilitate comprehension of the story, and motivate students in the learning process. The study was conducted at Pekuncen Elementary School in Pasuruan City, with 18 fifth-grade students as subjects. The method used was Classroom Action Research (CAR), implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation, storytelling skills tests, student interviews, and documentation of the learning process. The results showed a significant improvement in students' storytelling skills. Learning completion increased from 44.44% in the pre-cycle to 66.67% in the first cycle, and reached 88.88% in the second cycle. This improvement included aspects of speaking fluency, the use of a more varied vocabulary, coherent story structure, and the ability to convey appropriate expression and intonation. Furthermore, this approach encourages students to participate more actively in learning, increases self-confidence, and fosters courage in expressing opinions in class. These findings indicate that implementing Whole Language with the aid of illustrated ebooks is effective in developing elementary school students' storytelling skills. The combination of communicative learning methods and engaging media can create a fun, interactive, and meaningful learning environment. This study recommends that Indonesian language teachers at the elementary school level consider using a similar approach as an alternative strategy for teaching speaking skills, particularly in the context of storytelling.